An Optimum EOQ model for buyer-vendor with price breaks and fixed holding cost. Issue 1 (March 2021) - Muniappan, P.; Kirubhashankar, C.K.; Mohamed Ismail, A.
Abstract: In this paper, an EOQ model is developed for deteriorating product where constant demand depends on the buyer-vendor inventory level with price breaks. In traditional inventory problems, it is considered that the holding cost is fixed and setup cost is not subject to control. An inventory problem is formulated for deteriorating items, further, the optimal solutions are derived. Numerical examples presented to demonstrate the developed model. An algorithm is presented to determine the optimal inventory level while minimizing the present value of the total cost.